Mass realism? Developing a virtual ward round for medical students. (24th May 2012) - Bate, T; Kohlhoff, S; Dixon, J; Walters, D; Round, J
Abstract : Aims: Undergraduate paediatric attachments are typically 5-9 weeks long. As a result of changes in service delivery, it is an increasing challenge to expose students to the process of healthcare delivery and practical management of the unwell child. We sought to develop, use and evaluate a web-based tool to mimic aspects of a daily ward round, so that students could see how a child is assessed and managed over the course of an admission in an interactive and supportive environment. Methods: A virtual ward round (VWR), written in html, was delivered through a web browser by a facilitator.1 The VWR consisted of daily 30 minute sessions during the first week of a 4th year paediatric attachment. Participants were shown a virtual ward, and jointly conducted a ward round of 4 patients. Led by the facilitator, groups perused clinical information, discussed investigation results, considered disease processes and planned management. Developments were reviewed the following day. If patients were discharged, a new patient occupying the same bed would be introduced. Feedback was collected at the end of 6 separate attachments. Students rated sessions for content and presentation on a Likert scale from 1-5, chose appropriate adjectives and gave free text comments. Results: 28 VWR sessions were delivered over 6 attachments to a total of 221 students. The VWR mean content score was higher than the course mean (4.52 v 4.42). VWR presentation was rated higher than course mean: (4.41 v 4.17). The commonest adjectives chosen for VWR sessions were Interactive, Interesting, Engaging, Useful and Fun. Free text comments indicated that many students found the VWR the most valuable part of the week, and highlighted its breadth, realism and interactivity. Conclusions: The VWR successfully introduced students to paediatric clinical decision making, was well received and deemed particularly valuable. A web-based VWR enables students to experience common ward scenarios and is an effective adjunct to the teaching of clinical medicine.